Deep waters: Lessons from community meetings about offshore wind resource development in the U.S. (July 2015) - Hall, Damon M.; Lazarus, Eli D.
Abstract: Meeting the United States׳ offshore renewable-energy goals for 2030 necessitates deploying approximately 9000 wind turbines along U.S. coastlines. Because siting bottom-mounted turbines in most nearshore coastal zones is either impractical or politically difficult, turbine developers are testing floating-platform turbine technologies for deeper waters. Deepwater, floating-platform turbines have the advantages of being sited in the highest quality winds farther offshore, movable if desired, and located beyond the horizon, out of sight from shore. This paper reports on conversations with 103 coastal stakeholders at community meetings regarding development and testing of floating turbines off the coast of Maine, U.S.A. Using naturalistic field methods, this essay reports common questions and concerns of commercial lobstermen, fishermen, and coastal civic leaders. Early-stage conversations suggest that once coastal community members understand the benefits and impacts of wind farm development on their quality of life, many share specific preferences for where offshore developments could be located. Citizens׳ remarks are sophisticated, nuanced, and innovative and include robust ideas for pairing turbine siting with fishery conservation. Findings imply that when looking to site offshore turbines in public, multiple-use ocean spaces, developers, planners, and coastal communities should engage early and often in two-way conversation rather than one-way outreach. Highlights: We report local reactions to the U.S.'s first deepwater offshore floating wind turbine. Citizen questions and concerns about offshore wind are categorized into four themes. Communities have relevant knowledge and ideas to improve offshore wind turbine siting. Research can improve communication between developers and coastal stakeholders. Suggestions are made to improve stakeholder engagement concerning U.S. offshore wind.